Inmate Empowerment Through Training in Making Bags Made of Rope as a Provision of Skills - Dewi, Triana Kumala; Sholihah, Rosi Ayu; Sarie, Aries Luvieta; Kiswardinata, R. Bekti; Tri Prasasti, Pinkan Amita (International Journal of Community Service Learning, 2018)
Community service team, Elementary School Teacher Education Universitas PGRI Madiun has conducted training in making bags made from raw rope for inmates in prison Ngawi class II B as a provision of skills. The purpose of the abdimas is (1) Provision of skills to the prisoner by inviting the prisoners to perform a creation in the form of a rope bag (2) to create economic independence for the prisoners through training on making bags made from rope, (3) to encourage or support the prisoner again have confidence. Training activities begin with the opening and delivery of materials and discussion and evaluation. Training in making bag made from rope made with direct practice in bag making. Training training is emphasized on improving skills and motivational motivation for prisoners to remain confident in their work. It can be concluded that in the training of making bags made from raw rope has been done with bai. Based on the questionnaire results, 86% of participants gave an assessment that the training of bag making made from raw ropes for prisoners in Ngawi Class II class B institution is very motivating in increasing the skills of the participants.